Modelling the drought impact on monoterpene fluxes from an evergreen Mediterranean forest canopy. - Grote, Rüdiger; LAVOIR, ANNE-VIOLETTE; Rambal, Serge; Staudt, Michael; Zimmer, Ina; Schnitzler, Jörg-Peter (Oecologia, 2009)
In many ecosystems drought cycles are common during the growing season but their impact on volatile monoterpene emissions is unclear. Therefore, we aimed to develop and evaluate a process-based modelling approach to explore the explanatory power of likely mechanisms. The biochemically based isoprene and monoterpene emission model SIM-BIM2 has been modified and linked to a canopy model and a soil water balance model. Simulations are carried out for Quercus ilex forest sites and results are compared to measured soil water, photosynthesis, terpene-synthase activity, and monoterpene emission rates. Finally, the coupled model system is used to estimate the annual drought impact on photosynthesis and emission. The combined and adjusted vegetation model was able to simulate photosynthesis and monoterpene emission under dry and irrigated conditions with an R(2) of 0.74 and 0.52, respectively. We estimated an annual reduction of monoterpene emission of 67% for the extended and severe drought period in 2006 in the investigated Mediterranean ecosystem. It is concluded that process-based ecosystem models can provide a useful tool to investigate the involved mechanisms and to quantify the importance of specific environmental constraints.
Keywords: Biological; Carbon dioxide; Carbon Dioxide: metabolism; Computer Simulation; Drought impact; Droughts; France; Model coupling; Models; monoterpene emission; Monoterpenes; Monoterpenes: metabolism; photosynthesis; Photosynthesis: physiology; Plant Leaves; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: metabolism; Scaling; Trees; Trees: metabolism; water; Water: metabolism

Modeling volatile isoprenoid emissions – a story with split ends - Grote, R; Niinemets, Ü (Plant Biology, 2008)
Accurate prediction of plant-generated volatile isoprenoid fluxes is necessary for reliable estimation of atmospheric ozone and aerosol formation potentials. In recent years, significant progress has been made in understanding the environmental and physiological controls on isoprenoid emission and in scaling these emissions to canopy and landscape levels. We summarize recent developments and compare different approaches for simulating volatile isoprenoid emission and scaling up to whole forest canopies with complex architecture. We show that the current developments in modeling volatile isoprenoid emissions are “split-ended” with simultaneous but separated efforts in fine-tuning the empirical emission algorithms and in constructing process-based models. In modeling volatile isoprenoid emissions, simplified leaf-level emission algorithms (Guenther algorithms) are highly successful, particularly after scaling these models up to whole regions, where the influences of different ecosystem types, ontogenetic stages, and variations in environmental conditions on emission rates and dynamics partly cancel out. However, recent experimental evidence indicates important environmental effects yet unconsidered and emphasize, the importance of a highly dynamic plant acclimation in space and time. This suggests that current parameterizations are unlikely to hold in a globally changing and dynamic environment. Therefore, long-term predictions using empirical algorithms are not necessarily reliable. We show that process-based models have large potential to capture the influence of changing environmental conditions, in particular if the leaf models are linked with physiologically based whole-plant models. This combination is also promising in considering the possible feedback impacts of emissions on plant physiological status such as mitigation of thermal and oxidative stresses by volatile isoprenoids. It might be further worth while to incorporate main features of these approaches in regional empirically-based emission estimations thereby merging the “split ends”.
Keywords: BVOC emission; Isoprenoids; Modeling; Scaling; Spatial variability; temporal variability

Sensitivity of volatile monoterpene emission to changes in canopy structure: a model-based exercise with a process-based emission model - Grote, Rüdiger (New Phytologist, 2007)
* • This paper investigates the dependence of monoterpene emissions at the canopy scale on total leaf area and leaf distribution. Simulations were carried out for a range of hypothetical but realistic forest canopies of the evergreen Quercus ilex (holm oak). * • Two emission models were applied that either did (SIM-BIM2) or did not (G93) account for cumulative responses to temperature and light. Both were embedded into a canopy model that considered spatial and temporal variations of foliage properties. This canopy model was coupled to a canopy climate model (CANOAK) to determine the micrometeorological conditions at the leaf scale. * • Structural properties considerably impacted monoterpene emission. The sensitivities to changes in total leaf area and to leaf area distribution were found to be of similar magnitude. The two different models performed similarly on a whole-year basis but showed clear differences during certain episodes. * • The analysis showed that structural indices have to be carefully evaluated for proper scaling of emission from leaves to canopy. Further research is encouraged on seasonal dynamics of emission potentials.
Keywords: Biological; biomass; foliage distribution; leaf area index; light; Models; monoterpene emission; Monoterpenes; Monoterpenes: metabolism; photosynthesis; Photosynthesis: radiation effects; Plant Leaves; Plant Leaves: metabolism; Plant Leaves: radiation effects; Quercus; Quercus ilex; Quercus: metabolism; Quercus: radiation effects; Scaling; stand density; Temperature; Time Factors; Volatilization